Dead or alive - Landy, Derek (Landy, Derek. Skulduggery Pleasant, 2021)
With their enemies trying to bring back humankind's ancient overlords and return the Faceless Ones to power, Skullduggery Pleasant and Valkyrie Cane are the only ones who can stop them. To do so, they must assassinate Damocles Creed, but as Valkyrie wavers on her decision, the fate of the world hangs in the balance.